ABOUT SOME PROBLEMS GEOMETRY OF FOOT DRAWING (Pedagogy of Higher and Secondary Education, 2022)
The tasks of construction of geometrical elements by the division of corners are examined in the article. A method passed the tests on employment on drawing on the fine-art faculty of the Kryvoy Rog state pedagogical university.
Keywords: geometrical drawing; division of circumference; squaring of circle